1981
DOI: 10.1111/j.1476-5381.1981.tb09997.x
|View full text |Cite
|
Sign up to set email alerts
|

INCREASE OF ACETYLCHOLINE‐RECEPTOR SENSITIVITY BY ADENOSINE TRIPHOSPHATE: A NOVEL ACTION OF ATP ON ACh‐SENSITIVITY

Abstract: 1 The sensitivity of the nicotinic acetylcholine (ACh)-receptor, measured as the amplitude of ACh-current induced by iontophoretic application of ACh to the frog skeletal muscle endplate, was increased by the action of adenosine triphosphate (ATP). 2 This potentiation was not due to the effect of ATP on ACh-esterase, since the increase of the sensitivity could also be demonstrated by use of carbachol (CCh). 3 Kinetic analysis of the effect of ATP on the dose-response curve of CCh-current suggests that ATP incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
2

Year Published

1983
1983
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(43 citation statements)
references
References 4 publications
3
38
2
Order By: Relevance
“…This was confirmed by AKASU et al [4], who analyzed the facilitatory action of ATP on the sensitivity of nicotinic ACh-receptors. The amplitude of the ACh-current recorded at the frog skeletal muscle end-plate was increased by ATP.…”
Section: A) Experimental Evidencesupporting
confidence: 63%
See 1 more Smart Citation
“…This was confirmed by AKASU et al [4], who analyzed the facilitatory action of ATP on the sensitivity of nicotinic ACh-receptors. The amplitude of the ACh-current recorded at the frog skeletal muscle end-plate was increased by ATP.…”
Section: A) Experimental Evidencesupporting
confidence: 63%
“…This potentiation was not due to an effect of ATP on cholinesterases, since the increase of sensitivity could also be demonstrated with carbachol. Kinetic analysis of the effect of ATP on the dose-response relationship of the carbachol-current indicated that ATP increased the ACh-sensitivity without changing the affinity of ACh for its recognition site [4,5].…”
Section: A) Experimental Evidencementioning
confidence: 99%
“…Therefore, the present results support a hypothesis that substance P may be a modulator of the sensitivity of the nicotinic receptor in cholinergic transmission. The present paper, together with recent reports on the action of 5-hydroxytryptamine (Akasu et al, 1981a), catecholamine (Koketsu et aL, 1982a, b, c) and adenosine triphosphate (Akasu et al, 1981b) provide important experimental evidence showing that the sensitivity of a receptor for its agonist can be modulated by the action of other neurotransmitters or neurohormones.…”
Section: Discussionmentioning
confidence: 97%
“…The op posite process is that of sensitization (Karczmar and Howard 1955;Karczmar 1957Karczmar , 1987 . Both processes are due to an allosteric receptor change (Akasu et al 1981); in the case of desensitization, this change may be medi ated by the activation of one or more kinases by a non cholinergic transmitter (Greengard 1987;see, however, Colquhoun et al 1990). …”
Section: Interactions Modulations and Gene Expressionmentioning
confidence: 99%
“…The term modulation, defined first by Kyo Ko ketsu, Les Blaber, and this author (Karczmar et al 1972;Karczmar 1990;Akasu et al 1981) Thesleff (1955) and Karczmar and Howard (1955) . The effect in question was desensitization or receptor inac tivation arising from prolonged application of depolar izers, including ACh, to the motor endplate .…”
Section: Interactions Modulations and Gene Expressionmentioning
confidence: 99%